KONSEP PENARI DAN DESAIN RUANG PADA TARI MERENUNGKU ADALAH GERAK - Rochayati, Rully (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The writing is titled Concept of Dancers and Spatial Design on Dancing My Dream Is Motion. A writing that contains about the study of a work of dance that is discussed from the perspective of the study of the concept of dancers and spatial design. the whole work of dance is discussed in the concept of dancers by dividing the subject among other aspects of the number of dancers, sex and posture aspects, aspects of the unity of the composition of the group again termed the facet of the direction of the dancer, the